Between Justice and Certainty: Rethinking the Essence of Criminal Election Law Enforcement in South Sulawesi - Firmansyah, Hendra; Rahman, Sufirman; Husen, La Ode; Razak, Askari (Journal of Cultural Analysis and Social Change, 2025)
This study examines the urgency and effectiveness of criminal law enforcement in Indonesian general elections, with a case study in South Sulawesi Province. The research aims to: (1) analyze the importance of criminal election law enforcement in realizing justice, legal certainty, and utility, and (2) evaluate its effectiveness in practice. A normative–empirical mixed-methods design was employed by integrating doctrinal legal analysis with descriptive qualitative and quantitative approaches. Primary data were obtained through interviews, observations, and questionnaires administered to Bawaslu commissioners, members of the Gakkumdu Center, legal practitioners, academics, and community representatives across several districts/cities. Secondary data were derived from literature studies, official documents, and court rulings. The findings indicate that while the urgency of criminal election law enforcement is very high, its actual effectiveness in South Sulawesi remains low. Key constraints include: (1) legal provisions that impose relatively mild sanctions and short investigation deadlines; (2) weak institutional coordination within Gakkumdu and the absence of coercive authority, particularly detention powers. Drawing on the theoretical perspectives of Radbruch, Friedman, Soekanto, and Rahardjo, the study concludes that effective electoral criminal law enforcement requires a balanced interaction between legal substance, enforcement structures, and societal legal culture, supported by a progressive approach oriented toward substantive justice. The study recommends regulatory and institutional reforms particularly revisions to Law No. 7 of 2017 enhanced inter-agency coordination, and the development of a participatory legal culture to ensure fair, integrity-based, and dignified elections.